NARRATOLOGICAL STRATEGIES OF UKRAINIAN MAGICAL FOLKLORE - Івановська, Олена (Taras Shevchenko National University of Kyiv (Ukraine), 2021)
[Parubiy U. Yu. Ukrainian Order-Spell Poetry: Structural-Semantic Features and Poetics of the Genre. A Thesis for a Candidate Degree in Philological Studies. Lviv : Ivan Franko National University of Lviv, 2019. 198 p.]

[Парубій У. Ю. Українська замовляльно-заклинальна поезія: структурно-семантичні особливості та пое-тика жанру : дис. канд. філол. наук. Львів : Львів. нац. ун-т ім. Івана Франка, 2019. 198 с.]
НАРАТОЛОГІЧНІ СТРАТЕГІЇ УКРАЇНСЬКОГО МАГІЧНОГО ФОЛЬКЛОРУ